Validitas Instrumen Tes Kemampuan Berpikir Kritis Matematis Berdasarkan Teori FRISCO - Hamidah Suryani Lukman; Ana Setiani; Nur Agustiani (SJME (Supremum Journal of Mathematics Education), 2023)
This study aims to analyze the content validity of the test instrument for the mathematical critical thinking ability of junior high school students using the FRISCO indicator as an alternative solution to help teachers realize learning that develops students' mathematical critical-thinking ability. This study uses the Research and Development method with the ADDIE model. However, the stages are limited to the ADD (Analysis, Design, and Development). The instrument used an instrument validation sheet consisting of three assessment aspects: content feasibility assessment, language aspect assessment, and assessment of the suitability of items with FRISCO indicators, presented in 26 questions. The validation was carried out by five Experts in Mathematics Education Experts using the Delphi technique. Data were analyzed descriptively. Based on the results of data analysis, the product of the mathematical critical thinking ability test instrument with the FRISCO theory, 92% have met the content feasibility assessment criteria and are categorized as very valid. In the aspect of language feasibility, 86.60% of the assessment criteria have been met and classified as very valid categories. In the aspect of the suitability of the items with the FRISCO indicators, 92.20% of the assessment criteria have been met and classified as very valid categories. Thus, overall, 90.20% of the criteria for assessing the feasibility of the critical thinking ability test instrument with the FRISCO theory have been met and classified as very valid categories, and are suitable for use in learning.